Efficacy and Safety of Ultrasound-Guided Percutaneous Polidocanol Sclerotherapy in Benign Cystic Thyroid Nodules: Preliminary Results - Xiaohua Gong; Qi Zhou; Fang Wang; Wenjun Wu; Xiaojun Chen (International Journal of Endocrinology)
Objective. To evaluate the efficacy and safety of percutaneous polidocanol injection (PPI) in treating cystic thyroid nodules. Materials and Methods. A total of 158 cystic or predominantly cystic thyroid nodules (>80% cystic component) in 143 patients were evaluated. 114 patients with compressive symptoms or aesthetic complaints were offered PPI. 44 individuals without compressive symptoms and aesthetic complaints who were only followed up clinically were used as the control group. The efficacy and safety of PPI were evaluated for 1 month, 3 months, 6 months, 9 months, and 12 months of follow-up. Results. In the PPI group, the mean baseline volume of 15.6±18.9 cm3 reduced at the 1-month follow-up to 5.1±5.6 cm3 (p<0.001) and 0.6±0.9 (p<0.001), and nodules shrunk according to the time after PPI (p<0.001). A complete response (if ≥70% decrease) to PPI at the 12-month follow-up occurred in 100% of the cystic or predominant cystic nodules. None of the nodules recurred at the 12-month follow-up after PPI. The side effects were mild. Twenty patients (17.5%) developed mild localized pain, and fourteen cases (12.3%) experienced mild or moderate fever after PPI. Conclusions. PPI is a safe and effective alternative to treat benign cystic or predominant cystic thyroid nodules.